Clinical study of nail changes in vitiligo. (26th February 2013) - Anbar, Tag; Hay, Rania Abdel; Abdel‐Rahman, Amal T; Moftah, Noha H; Al‐Khayyat, Mohamed A
Summary Both vitiligo and alopecia areata (AA) are associated together, associated with other autoimmune diseases, and autoimmunity is one of the important theories in their etiology. Nail changes are a known association with AA, thus we hypothesized that nail changes can be found in vitiligo patients. On revising the literature, only two types of nail changes were described in association with vitiligo. Our aim was to study the frequency and types of nail changes among vitiligo patients in comparison with normal healthy volunteers. This multi‐centric study was carried on 91 patients with vitiligo, as well as 91 normal healthy control subjects who were age‐ and sex‐matched. Nails were examined for changes in nail plates as regards striations, texture, curvature, dystrophy, and pigmentation. The presence or absence of the thumb lunula was also reported. Nail changes were observed in 62 patients (68.1%) and 46 (50.5%) control subjects with a statistically significant difference (P = 0.016). Longitudinal ridging and absent lunula were significantly higher in patients than in the controls (P = 0.001 and 0.037, respectively). Other reported nail abnormalities in the current study included punctate leukonychia, pitting, flag sign, and Terry's nails. Awareness of this association will widen the clinician's perspective to carefully examine the nail changes in vitiligo patients and conversely examine patients with nail changes for vitiligo.